Treatment plan robustness in pancreatic patients treated with scanned ion-beam therapy: inter- and intra-fractional aspects - Batista, Vania (2018)
Keywords: Radiation Therapy, Ion Therapy, Treatment Planning, Motion Management, Pancreas, Schwerionentherapie
Keywords: Hochschulschrift